2012
DOI: 10.4314/agrosh.v11i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Usage of Upgraded Indigenous Shea Butter Processing Technology by Women Processors in Kwara State, Nigeria

Abstract: The study was carried out in Agbaku-Eji

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
3
4
1
Order By: Relevance
“…This conforms to the findings of (Daudu, 2016), that the higher the educational status of the farmers the higher their likelihood to be involved in soil fertility management practices. However, this finding is contrary to the findings of Matanmi et al (2011) where no significant relationship was found between socio economic characteristics of respondents and the level of usage of new technology given to farmers. This could be attributed to the fact that education increases human understanding, knowledge and capacity to acquire skills.…”
Section: Extent Of Usage Of Soil Conservation Practices By Respondentscontrasting
confidence: 57%
“…This conforms to the findings of (Daudu, 2016), that the higher the educational status of the farmers the higher their likelihood to be involved in soil fertility management practices. However, this finding is contrary to the findings of Matanmi et al (2011) where no significant relationship was found between socio economic characteristics of respondents and the level of usage of new technology given to farmers. This could be attributed to the fact that education increases human understanding, knowledge and capacity to acquire skills.…”
Section: Extent Of Usage Of Soil Conservation Practices By Respondentscontrasting
confidence: 57%
“…On educational status, the results revealed that majority of them were not literate with a percentage of 86% having no formal education. This finding agrees with the report of Matanmi et al, (2011) who also found that most shea butter producers were not educated. This low level of education may affect their adoption of new practices such as improved processing methods since it is asserted that being educated enables farmers to understand more easily the use of improved technologies (Tshivunza, et al, 2001).…”
Section: Resultssupporting
confidence: 93%
“…The pooled results (Table 1) for the marital status of the respondents showed that most of the respondents were married (95.3%). The finding agrees with the results of Matanmi et al, (2011) who reported that most shea butter producers were married. The fact that almost all those involved in shea butter production were married was an indication that shea butter production might be regarded as a domestic chore for married women in the study area.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations